Analisa Pengujian Kekerasan pada Cakram Rem Motor Yamaha Matic - Dede Iman Saputra; Maulana Rachman; Sandi Ramadhan; Suparno Suparno (International Forum of Researchers and Lecturers, 2026)
The brake system on a vehicle is an important component for driving safety, brake malfunction can cause danger and driving safety is disturbed to the point of failure which can cause serious accidents. The object of the study was chosen original brake discs and variation discs used for Yamaha Matic Mio motorbikes. in the general public it is better known as brake discs, Hardness testing was carried out using the Rockwell method with 10 pressure points on the braking friction area with an average value of the original disc with a value of 57 HRC, and the value of the variation disc with a value of 53 HRC with a slight difference of 4 HRC, Brinell hardness value and the original disc tensile test averaged 586 HBS and the average variation disc value was 501 HBS. while the conversion tensile test value from the Rockwell hardness test value on the original disc was 1645 N / mm² and the variation disc brake was 1597.2 N / mm² thus the Rockwell test value, Brinell conversion and the original disc tensile test were still greater than the variation disc tensile test value.